Exploring alternative education: a comparison on 3 levels—Waldorf charters, non-Waldorf charters, and local public schools, as measured by the California Assessment of Student Performance and Progress - Telfer-Radzat, Kimberly (Frontiers in Education, 2024)
This quantitative, causal-comparative study examines the significance of the levels of achievement in English language arts (ELA) and math among students enrolled in 16 Waldorfinspired charter schools and other charter and non-charter public schools in California, using the California Assessment of Student Performance and Progress (CAASPP) scores. The number of charter schools in California has increased by three percent (by approximately 2,500 schools) between 2009 and 2019 (NCES.ed.gov, 2022). Waldorf-inspired charter schools, a growing branch of the traditionally private 100-year-old Waldorf school movement, are among those growing throughout California. This study finds that by eighth grade a significantly higher percentage of students in Waldorf-inspired charter schools are meeting or exceeding state standards in ELA and math as compared to their non-Waldorf charter school comparison groups.